Serum peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 in combination with C-reactive protein and white blood cell as novel predictors for infants with community-acquired pneumonia - Heng Xue; Hui Liu; Liangpu Xu; Qiaoling Liu; Bimin Zhuo; Meifeng Dai; Zhihui Wu; Min Chen; Qingquan Chen (European Journal of Inflammation, 2020)
The aim of this study was to investigate the predictive value of peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (Pin1) with C-reactive protein (CRP) and white blood cell (WBC) count for community-acquired pneumonia (CAP) in infants. A total of 84 hospitalized infants with CAP and 69 healthy infants were included in this study. The clinical manifestations and laboratory assay results of infants were recorded. Serum Pin1 level was estimated by enzyme-linked immunosorbent assay. The median serum Pin1 concentration in infants with CAP was significantly higher than that in controls (1.44 vs. 0.21 ng/mL, P  < 0.0001). Receiver operating characteristic (ROC) curve analysis showed that the area under the ROC curve (AUC) of the combination Pin1, CRP and WBC (Pin1 + CRP + WBC, 0.943) was higher than Pin1, CRP, WBC alone or the combination of Pin1 and CRP ( P  < 0.05). The sensitivity of Pin1 + CRP + WBC (94.0%) was higher than that of Pin1, CRP, WBC alone, or any two combined ( P  < 0.05). Pin1 + CRP + WBC also had a high negative predictive value (91.4%). Moreover, serum Pin1 alone had a high specificity (97.0%) and excellent positive predictive value (96.6%) for infants with CAP, which were higher than WBC, Pin1 and WBC in combination, CRP and WBC in combination, and Pin1 + CRP + WBC ( P  < 0.05). Therefore, serum Pin 1 was highly expressed in infants with CAP and can singly or in combination with CRP and WBC represent promising novel predictors for infants with CAP.